2021
DOI: 10.1017/s0043887121000083
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Political Apologies on Public Opinion

Abstract: Apology diplomacy promises to assuage historical grievances held by foreign publics, yet in practice appears to ignite domestic backlash, raising questions about its efficacy. This article develops a theory of how political apologies affect public approval of an apologizing government across domestic and foreign contexts. The authors test its implications using large-scale survey experiments in Japan and the United States. In the surveys, the authors present vignettes about World War II grievances and randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 86 publications
0
14
0
Order By: Relevance
“…Referring to this trend, Gibney et al (2009) called the present era the “age of apology.” Accordingly, a growing number of scholars are paying attention to political apologies and examining their effect on victims’ perceptions of the perpetrator group. Some studies have been based on in-depth qualitative analysis of historical cases (Lind, 2009, 2011; Long and Brecke, 2003), but the majority of studies are quantitative (Blatz et al, 2009, 2014; Hornsey and Wohl, 2013; Kitagawa and Chu, 2021; Okimoto et al, 2015; Paez, 2010; Philpot and Hornsey, 2008, 2011; Wohl et al, 2012, 2013).…”
Section: Theories On Political Apologymentioning
confidence: 99%
See 2 more Smart Citations
“…Referring to this trend, Gibney et al (2009) called the present era the “age of apology.” Accordingly, a growing number of scholars are paying attention to political apologies and examining their effect on victims’ perceptions of the perpetrator group. Some studies have been based on in-depth qualitative analysis of historical cases (Lind, 2009, 2011; Long and Brecke, 2003), but the majority of studies are quantitative (Blatz et al, 2009, 2014; Hornsey and Wohl, 2013; Kitagawa and Chu, 2021; Okimoto et al, 2015; Paez, 2010; Philpot and Hornsey, 2008, 2011; Wohl et al, 2012, 2013).…”
Section: Theories On Political Apologymentioning
confidence: 99%
“…However, such an apology may not be optimal considering domestic politics and relations with countries other than the victimized one. Several studies, for example, have pointed out that certain apology elements are prone to spark a backlash from the perpetrator country's citizens, mainly from those who are high in social dominance orientation, which then reduces the apology's effectiveness (Kitagawa and Chu, 2021; Lind, 2011; Mifune et al, 2019; Ohtsubo et al, 2021). Therefore, in analyzing international apologies, it is also important to consider how significant each apology element is for the victimized country's citizens.…”
Section: Theories On Political Apologymentioning
confidence: 99%
See 1 more Smart Citation
“…Japan has also been examined as a key case to address general, substantive questions in areas such as trade policy and the evolution of the international order (Davis, 2003;Naoi, 2015;Lipscy, 2017;Goddard, 2018;Funabashi and Ikenberry, 2020). Another common approach is to leverage some feature of Japan advantageous for causal inferencee.g., as-if random assignment of attributes such as the timing of municipal elections and candidate surnamesor to conduct survey experiments on Japanese subjects to examine questions of broader significance (Fukumoto and Horiuchi, 2011;Fukumoto and Miwa, 2018;Kitagawa and Chu, 2021).…”
Section: Three Responses To Skepticismmentioning
confidence: 99%
“…This social harmony is reflected on positive perceptions of emotional climate by victims when they are involved in reparato ry activities (Páez, Espinosa, & Bobowik, 2013), reporting positive social well-being (Rimé et al, 2011), positive perceived emotional climate and intentions to support the apologisers' policies (Shnabel & Nadler, 2008). Subsequent studies have, indeed, confirmed that victim-inclusive forms of apology gain more political support than victim-exclusive forms, because of better psychosocial healing and more highly perceived repair of the wrongdoing (Blatz & Philpot, 2010;Blatz et al, 2009;Kitagawa & Chu, 2021). Likewise, Berndsen et al (2015) suggested that victim-focused apologies yield more positive outcomes in terms of support, forgiveness and perceived sincerity of offenders than offender-focused apologies.…”
Section: Interaction Between Offenders and Victims As Part Of Politic...mentioning
confidence: 99%